Biopharmaceutical characterization of decursin and their derivatives for drug discovery. (October 2013) - Mahat, Bimit; Chae, Jung-woo; Baek, In-hwan; Song, Gyu-yong; Song, Jin-sook; Ma, Jin-yeul; Kwon, Kwang-il
Abstract : Angelica gigas Nakai and its components are known to have neuroprotective, antiplatelet, and anticancer activities. The present study evaluated the in vitro and in vivo biopharmaceutical characterization of Angelica gigas component substances, including decursin (the main substance), decursinol angelate (decursin isomer), JH714 (ether form of decursin) and epoxide decursin (epoxide form of decursin). Decursin, decursinol angelate and JH714 exhibited acceptable metabolic stability (>50%) in liver microsomes from human and higher bound fraction (>90%) in human plasma operating ultrafiltration. Decursin and decursinol angelate in CYP1A2 and CYP2C19 indicated less than 50% CYP activity, suggesting inhibition of the CYP isoforms using Vivid ® CYP screening kit. JH714 only showed an apparent permeability coefficient of <10 × 10 −6 cm/s in MDCK cells, suggesting that it is poorly absorbed. Blood brain barrier permeability was examined after oral administration to male Sprague–Dawley (SD) rats, and pharmacokinetic studies were performed after oral and intravenous administration of 10 mg/kg compounds. Decursin, decursinol angelate and JH714 showed ratios of compound concentration in brain with respect to plasma (Cbrain /Cplasma ) of >1.5, suggesting good brain/plasma ratio at 0.5, 1, 3, and 5 h. In contrast, Cbrain /Cplasma was <0.5 for epoxide decursin. For all test compounds, >1.5% of the dose remained in GI tract after 8 h, and the excretion rate in urine was <0.5% which suggests that gastro intestinal tract may be major site of disposition following oral administration. Finally, these results may be useful for the design of dosage regimens of decursin and its derivatives.